Patellofemoral osteoarthritis coexistent with tibiofemoral osteoarthritis in a meniscectomy population. Issue 12 (20th April 2005) - Englund, M; Lohmander, L S
Abstract : Objectives: To evaluate the frequency of patellofemoral osteoarthritis and its relevance to symptoms and function in a meniscectomy population. Methods: 317 patients with no cruciate ligament injury were evaluated (mean (SD) age, 54 (11) years). They had undergone meniscal resection 15 to 22 years earlier (follow up rate 70%). Standing tibiofemoral and skyline patellofemoral radiographs were graded according to the OARSI atlas. The Knee Injury and Osteoarthritis Outcome Score (KOOS) was used to quantify symptoms and function. Controls were 68 unoperated subjects identified from national population records. Results: Patellofemoral osteoarthritis (isolated or coexisting with tibiofemoral osteoarthritis) was present in 66 of 317 index knees (21%) and 21 of 263 unoperated contralateral knees (8%, p<0.001). In 57/66 (86%) of these index knees, tibiofemoral osteoarthritis was present (mixed osteoarthritis). In a model adjusted for age, sex, and body mass index, the odds ratio for patellofemoral osteoarthritis (alone or in combination with tibiofemoral osteoarthritis) was 2.6 (95% confidence interval, 1.1 to 6.6) after medial meniscectomy and 5.3 (1.9 to 15.0) after lateral meniscectomy, using controls as the reference. Individuals with a mixed knee osteoarthritis pattern had more symptoms, lower function in sports and recreation, and worse knee related quality of life than subjects with isolated tibiofemoral osteoarthritis. Conclusions: Mixed patellofemoral and tibiofemoral osteoarthritis is common in a meniscectomy population. Patellofemoral osteoarthritis is a contributing cause of knee symptoms and reduced knee related quality of life and is relevant to the management of knee complaints of this group of patients.